2010
DOI: 10.1136/tc.2009.035584
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine reduction revisited: science and future directions

Abstract: Regulation of nicotine levels in cigarettes and other tobacco products is now possible with the passage of the Family Smoking Prevention and Tobacco Control Act (FSPTCA) in 2009 giving the U.S. Food and Drug Administration authority to regulate tobacco products, and with Articles 9-11 of the World Health Organization Framework Convention on Tobacco Control.[1-2] Both regulatory approaches allow establishing product standards for tobacco constituents, including nicotine. The FSPTCA does not allow nicotine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 142 publications
3
88
0
Order By: Relevance
“…Benowitz and Henningfield (1994) originally recommended a reduction in nicotine levels of all cigarettes over the course of 10-15 years, although recent studies have demonstrated that immediate reduction is also successful in decreasing smoking and even dependence (Donny, Houtsmuller, & Stitzer, 2007;Hatsukami et al, 2010). While arguments could be made for either reduction strategy, the rate of reduction may substantially impact the level to which nicotine content would need to be reduced.…”
Section: Dose-response Curves For Acquisition and Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…Benowitz and Henningfield (1994) originally recommended a reduction in nicotine levels of all cigarettes over the course of 10-15 years, although recent studies have demonstrated that immediate reduction is also successful in decreasing smoking and even dependence (Donny, Houtsmuller, & Stitzer, 2007;Hatsukami et al, 2010). While arguments could be made for either reduction strategy, the rate of reduction may substantially impact the level to which nicotine content would need to be reduced.…”
Section: Dose-response Curves For Acquisition and Maintenancementioning
confidence: 99%
“…Hatsukami et al, 2010). That is, some individuals may not stop smoking as a direct result of nicotine reduction, possibly because the nicotine content in cigarettes remains above their individual threshold for reinforcement.…”
Section: Models Of Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the nicotine content in cigarettes to a non-addictive level has been suggested as a potential strategy for improving public health because it may decrease the prevalence of smoking (Benowitz and Henningfield, 1994;Hatsukami et al, 2010). A recently completed clinical trial on nicotine reduction showed that individuals who smoked very low nicotine content cigarettes for 6 weeks smoked fewer cigarettes and scored lower on measures of nicotine dependence compared with individuals who smoked cigarettes with a normal nicotine content .…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale research is needed to validate this instrument in the population of US college students. This research will enable the FDA to develop empirically derived standards for performance and quality control for hookah tobacco manufacturers with the goal of tobacco harm reduction (107), especially since the FDA is not authorized to ban tobacco products.…”
Section: Setting the Research Agendamentioning
confidence: 99%